Segmental duplications are hot spots of copy number variants affecting barley gene content. (17th May 2020) - Bretani, Gianluca; Rossini, Laura; Ferrandi, Chiara; Russell, Joanne; Waugh, Robbie; Kilian, Benjamin; Bagnaresi, Paolo; Cattivelli, Luigi; Fricano, Agostino
SUMMARY: Copy number variants (CNVs) are pervasive in several animal and plant genomes and contribute to shaping genetic diversity. In barley, there is evidence that changes in gene copy number underlie important agronomic traits. The recently released reference sequence of barley represents a valuable genomic resource for unveiling the incidence of CNVs that affect gene content and for identifying sequence features associated with CNV formation. Using exome sequencing and read count data, we detected 16 605 deletions and duplications that affect barley gene content by surveying a diverse panel of 172 cultivars, 171 landraces, 22 wild relatives and other 32 uncategorized domesticated accessions. The quest for segmental duplications (SDs) in the reference sequence revealed many low‐copy repeats, most of which overlap predicted coding sequences. Statistical analyses revealed that the incidence of CNVs increases significantly in SD‐rich regions, indicating that these sequence elements act as hot spots for the formation of CNVs. The present study delivers a comprehensive genome‐wide study of CNVs affecting barley gene content and implicates SDs in the molecular mechanisms that lead to the formation of this class of CNVs. Significance Statement: In the present study, we examined the diversity and distribution of CNVs that affect gene content in 397 diverse barley accessions. Leveraging the reference sequence of the barley cultivar 'Morex', we show that CNVs occur preferentially in SD‐rich regions.